Digital Ethics in Anime: A Critical Analysis of Light Yagami in Death Note for English Learning - Batubara, Lika Silvia; Wardana, Bendra (JOURNAL OF LANGUAGE, 2026)
The rapid advancement of digital technology has significantly transformed how individuals interact, make decisions, and engage with ethical issues, particularly within technology-driven environments. In educational settings, digital media has been widely utilized to support English language learning; however, its implementation has largely emphasized linguistic competence, often overlooking the development of students’ ethical awareness. Despite the growing integration of digital tools in English language teaching, their potential role in fostering ethical reasoning remains insufficiently explored, especially among students in computer-related disciplines. This gap underscores the need for a more integrative pedagogical approach that connects language acquisition with critical ethical reflection. This study aims to investigate how digital ethics is represented through the character Light Yagami in the anime Death Note and to examine its potential as a pedagogical resource in English language teaching. Employing a qualitative descriptive approach, the study applies literary analysis, digital ethics frameworks, and principles of English for Specific Purposes (ESP). The findings indicate that the character embodies central ethical issues such as power, justice, and responsibility, while illustrating how the misuse of authority can result in significant moral consequences. Furthermore, the analysis demonstrates that anime narratives can serve as an effective medium for engaging students with complex ethical dilemmas in technology-oriented contexts. The use of anime also provides meaningful and relatable contexts that enhance language comprehension and stimulate critical thinking. This study contributes to the intersection of digital ethics and ESP by positioning anime as an innovative pedagogical tool for promoting ethical engagement in English language learning.